The impact of persistent innovation on Australian firm growth. (1st September 2021) - Hendrickson, Luke; Taylor, David; Ang, Lyndon; Cao, Kay; Nguyen, Thai; Soriano, Franklin
Abstract : This paper assesses the contribution of innovation persistence to surviving Australian firm growth performance over the period 2007–08 to 2013–14 with the added advantages that new firms, micro-sized firms and all industry sectors are included in our analysis. Over this period, firms with high sales and/or employment growth accounted for the majority of aggregate economic and employment growth in Australia, which is consistent with similar studies in other countries. Using a randomized, stratified sample from a firm population-level database that links administrative, tax and survey data, we created a matched, balanced sample of surviving firms to show that short-term persistent innovators (particularly young SMEs) significantly outgrow their less persistent and non-innovator counterparts in terms of sales, value added, employment and profit growth. Persistent innovators are more likely to be high-growth firms and more likely to introduce multiple types of innovation that are more novel. Our findings suggest that broad-based innovation policies may support successive waves of high-growth firms that help to sustain economic and employment growth in Australia.